Nature-based solution for climate change adaptation and mitigation in urban areas with high natural risk: Proposals of possible measures for a municipality in the Vesuvius area - Mazzeo, Giuseppe; Polverino, Salvatore (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Nowadays, due to the problematic containment of pollutant emissions worldwide, the process of global warming is inevitable. Moreover, in urban environments, due to the strong anthropisation of the spatial context, these phenomena are often accentuated (e.g. urban heat islands). At the same time, the detrimental effects of the aforementioned process are often combined with other pre-existing risks linked to urbanisation in areas of high natural risk (e.g. hydrogeological and volcanic risk). In this context, the first examples of the application of measures for adaptation and mitigation of climate change in urban areas are recorded in formulating the latest generation of urban plans. In this respect, natural-based solutions (NBS) are becoming favoured. These measures have a twofold beneficial effect on the urban reality, i.e. adaptation to the effects of climate change and increased renaturalisation of the urban area, with consequent mitigation of other natural hazards. The present contribution aims to offer an analysis of the main NBSs applicable in an urban context and on different scales (from urban to building) and an applicative example related to their integration into territorial governance tools. In particular, the municipality of Cercola, a territorial context with a high natural risk in the Vesuvian area, has been analysed as a case study.